An Improved Prosthesis for Through Ankle Joint Amputation - Kadom Rasheed, Noon; Kahtan, Yassr Y. (Al-Khwarizmi Engineering Journal, 2024)
Prosthetics through the ankle joint are prescribed to patients with a Symes amputation after rehabilitation. Energy can be stored and discharged from the flexible parts, such as the foot, leg and joints of the prostheses. This work improves the prosthetics for amputation through the ankle joint by providing the prosthetics with a movable ankle joint. The most important achievement of the ankle joint is that it performs important walking movements, the most important being planter flexion, dorsiflexion, inversion and eversion. A movable ankle joint was suggested and modelled in the SOLIDWORK program, and it was analysed using the finite element method to evaluate stresses and deformations. This model was used to improve a patient’s gait and reduce exertion. The suggested ankle joint was evaluated through several experimental tests, such as the ground reaction force (GRF) test, 6 min walking test and range of motion test. All the results indicate an improvement in gait parameters and patient adaptation to the suggested ankle-joint prosthetic. The GRF test showed the behaviour of the normal state approaches when using the suggested ankle-joint prosthetic. The results of the GRF test illustrate the percentage difference in the forces for the healthy limb from the suggested movable prosthetic and thetraditional one, with approximate values of 10.96% and 38.88%, respectively. Calculation revealed that the weight of the movable prosthetic with the suggested ankle joint was reduced by 32.69% compared with traditional prosthetic. In addition, a questionnaire was conducted to determine the extent of patient satisfaction when the moving prosthetic was used for a certain period. The questionnaire presented a considerable improvement in patient comfort and other aspects compared with the traditional prosthetic.